Rancang Bangun Sistem Informasi Administrasi Kependudukan Berbasis Web Pada Desa Compreng, Kecamatan Widang, Kabupaten Tuban - Rohman, Moch. Abdul; Wahyuningtyas, Emmy (Informatics Department-Universitas Wijaya Kusuma Surabaya, 2022)
Population administration activities in Compreng Village, Widang District, Tuban Regency are handled by village government employees using office software, so they still encounter several problems including the presentation of information that is not organized, the making of letters is not automatic and others. Therefore, an information system is needed that can improve service quality and facilitate village government employees in carrying out population administration activities.The system proposed by the author is web-based, built with stages that refer to the waterfall method using Adobe Dreamweaver CC 2020 software using the PHP programming language and MySQL as the database. From the results of implementation to system testing using the blackbox method, the system managed to run all processes and features as planned properly.